Introduction to optical metrology - Sirohi, R. S. (Optical sciences and applications of light., 2016)
Introduction to Optical Metrology examines the theory and practice of various measurement methodologies utilizing the wave nature of light. The book begins by introducing the subject of optics, and then addresses the propagation of laser beams through free space and optical systems. After explaining how a Gaussian beam propagates, how to set up a collimator to get a collimated beam for experimentation, and how to detect and record optical signals.